The cepstral spectral index of dysphonia, the acoustic voice quality index and the acoustic breathiness index as novel multiparametric indices for acoustic assessment of voice quality. Issue 6 (December 2021) - Barsties v. Latoszek, Ben; Mathmann, Philipp; Neumann, Katrin
Abstract : Purpose of review: The objective assessment of voice quality using acoustic measures is an important pillar of voice diagnostics. This article reviews three recent acoustic measures and their clinical use in phoniatrics and laryngology. Recent findings: Two acoustic parameters, the cepstral spectral index of dysphonia (CSID) and the acoustic voice quality index (AVQI), have gained importance as validated multiparametric indices in the objective assessment of hoarseness because they include both continuous speech and sustained vowels. The acoustic breathiness index (ABI), another multiparametric index, assesses breathiness admixture during phonation and identifies it robustly, unaffected by other characteristics of dysphonia such as roughness. Summary: Acoustic measurements are useful diagnostic tools when used correctly with an appropriate recording system, consideration of environment and use of software programs. CSID, AVQI and ABI objectively improve the detection of voice quality abnormalities. In addition to their proven validity, their application is simple and their usability for clinicians is high.